2018
DOI: 10.1021/acsanm.8b00639
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Porosity in Copper-Based Multinary Sulfide Nanostructures for Energy, Biomedical, Catalytic, and Sensing Applications

Abstract: Copper-based multinary sulfides (CMSs) have been the subject of intense research over the past decade due to the numerous outstanding properties that emerge when they are synthesized on the nanoscale. CMS compounds (e.g., CuInS 2 , Cu 2 SnS 3 , Cu 12 Sb 4 S 13 , and Cu 2 ZnSnS 4 ) are best known for their immense potential in energy-related disciplines. Through nanoscale engineering, new and exciting opportunities have opened up for these materials to be used in a wider range of applications. This review accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 165 publications
0
18
0
Order By: Relevance
“…But since binary copper sulfides have already been examined extensively, it may be worth looking into their multinary derivatives, which are vast in number given that a myriad of combinations is possible when other metals are incorporated into the Cu–S system. Some of these multinary copper sulfide derivatives (e.g., Cu 2 SnS 3 , Cu 2 NiSnS 4 , CuCo 2 S 4 ) have already been studied as electrode materials for other energy storage systems, [ 89 ] but they remain unexplored as RMB cathodes except for Cu 2 MoS 4 . [ 46,98 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But since binary copper sulfides have already been examined extensively, it may be worth looking into their multinary derivatives, which are vast in number given that a myriad of combinations is possible when other metals are incorporated into the Cu–S system. Some of these multinary copper sulfide derivatives (e.g., Cu 2 SnS 3 , Cu 2 NiSnS 4 , CuCo 2 S 4 ) have already been studied as electrode materials for other energy storage systems, [ 89 ] but they remain unexplored as RMB cathodes except for Cu 2 MoS 4 . [ 46,98 ]…”
Section: Discussionmentioning
confidence: 99%
“…[27,88] Recent reports indicate that multinary compositions have the potential to dramatically outperform binary systems as electrodes for energy storage applications. [89] Aside from having higher electronic conductivity than binary compounds, richer redox chemistry and better charge redistribution can be realized in multinary compounds where more than one metal component are present. Thus, the use of multinary metal chalcogenides as cathodes for RMBs has also been explored lately.…”
Section: Other Metal Chalcogenidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experimental and theoretical studies demonstrated that Cu(100) is the most favorable crystal orientation for the C−C coupling process . However, the surface of Cu electrodes under electrochemical environments often undergoes reconstructions induced by applied potentials, the intermediates formed during CO 2 RR, as well as specifically adsorbed anions . On the other hand, some anions either present in the electrolyte or adsorbed on the electrode surface, have been shown to play a vital role in the dynamic evolution of the catalyst structure under reaction conditions as well as the activity and selectivity of CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] However,t he surface of Cu electrodes under electrochemical environments often undergoes reconstructions induced by applied potentials, [24][25][26] the intermediates formed during CO 2 RR, [27] as well as specifically adsorbed anions. [28][29][30] On the other hand, some anions either present in the electrolyte [12,31,32] or adsorbed on the electrode surface, [33] have been shown to play av ital role in the dynamic evolution of the catalyst structure under reaction conditions as well as the activity and selectivity of CO 2 RR. These important findings might be used in the design and development of new electrodes via electrochemical modifications.…”
Section: Introductionmentioning
confidence: 99%